SACRED FUNCTION OF THE FESTIVE PIE AMONG ANCIENT ROMANS: ONOMASIOLOGICAL AND CULTUROLOGICAL ASPECTS - Михайлова, Олена (Taras Shevchenko National University of Kyiv (Ukraine), 2023)
The article represents evolutional changes in modern culture of celebration, the traits of desacralization of traditional festive practices in comparison with the old ceremonial rites of "serving the deity" appropriate, in particular, to Greeks and Romans. In conformity with V. Turner’s universal theory of rite its multilevel structure was determined (symbolic, valuable, teleological and role-playing) as well as important sacred function that insures the integrity of all components. The rite of sacrifice was described as the most important festive ritual aimed at the creation of the channel of communication between the heavenly and the earthly, between gods and people. The assignment of different species of animals and plants’ sacrifice was determined the existence of link between the type of ophir and the deity’s cult was proved, between its zoomorphic and phytomorphic attributes, which had to guarantee the choice of the victim at the deity’s preference. Ancient Greeks and Romans traditionally sacrificed the bulls to Zeus / Jupiter, the cows to Hera / Juno, the horses to Poseidon / Neptune, the ear of cereals to Demeter / Ceres etc., and those who lacked the money to buy animals, had to choose animal and vegetable substitutes to bloody sacrifice – pies in the form of animalistic figures. The sacred assignment of festive banquet after the sacrifice ritual was grounded, when joint consumption of food symbolized an accord between gods and people and was aimed at winning support of the celestials and to ensure receiving divine favour. Names of bakery product were analyzed, in particular, pies, that ancient Romans used as bloodless sacrifice during both public sacrifice ceremony and festive rituals in the family circle. Conclusion was made that metaphthonyтy is major means of nomination, language formulas of dedication and examples of the use of pies’ names in the works of such famous Roman authors as Cato, Ovid, Horace, Martial and others were illustrated. Derivative mutuality of the names of festive pies and the libation as various types of the ophir deriving from the Latin verb "libare" – to sacrifice – was determined.

Представлено еволюційні зміни в сучасній культурі святкування, ознаки "десакралізації" традиційних святкових практик порівняно з давніми урочистими обрядами "служіння божеству", зокрема, властивими грекам і римлянам. Згідно з теорією ритуалу В. Тернера, визначено багаторівневу структуру (символьну, ціннісну, телеологічну й рольову) універсального феномену та важливу сакральну функцію, що забезпечує єдність усіх його складових. Окреслено обряд жертвоприношення як найважливіший святковий ритуал, метою якого було створити канал спілкування між небесним і земним, між богами й людьми. З'ясовано призначення різних видів тваринних і рослинних жертв, доведено існування зв'язку між видом офіри і культом божества, його зооморфними та фітоморфними атрибутами, що мало гарантувати вибір жертви за вподобаннями божества. Давні греки й римляни традиційно жертвували Зевсу / Юпітеру биків, Гері / Юноні – корів, Посейдону / Нептуну – коней, Деметрі / Церері – колосся злаків, а ті, у кого бракувало коштів для купівлі тварин, обирали тваринно-рослинні субститути кривавих жертв – пироги у формі анімалістичних фігурок. Обґрунтовано сакральну функцію святкового бенкету після обряду жертвоприношення, коли спільне споживання їжі символізувало злагоду між богами і людьми, мало на меті заручитися підтримкою небожителів, забезпечити отримання божественної милості. Проаналізовано назви борошняних виробів, зокрема, пирогів, що їх використовували давні римляни як безкровні жертви під час публічних жертвоприношень і святкових ритуалів у родинному колі. Зроблено висновок щодо метафтонімії як основного способу номінації, представлено типові мовні формули посвяти й наведено приклади вживання назв пирогів у творах таких відомих римських авторів, як Катон, Овідій, Горацій, Марціал та ін. Визначено дериваційну спільність назв святкових пирогів та узливань як різних видів офіри, що походять від латинського дієслова libare – жертвувати.
САКРАЛЬНА ФУНКЦІЯ СВЯТКОВОГО ПИРОГА У ДАВНІХ РИМЛЯН: ОНОМАСІОЛОГІЧНИЙ І КУЛЬТУРОЛОГІЧНИЙ АСПЕКТИ
Keywords: feast; ritual; sacrifice; ritual food; свято; ритуал; жертвоприношення; обрядова їжа